An energy and delay aware routing protocol for wireless sensor network assisted IoT to maximise network lifetime. (14th June 2022) - Vinmathi, M.S.; Josephine, M.S.; Jeyabalaraja, V.
IoT is a technology where different devices are connected and integrated to provide solutions. The ultimate source of gathering and processing a large data are obtained through sensor devices. In this research work, a protocol for routing is proposed which is aware of the delay and energy is a WSN (EDAR-WIoT) for lifetime maximisation in network. The proposed EDAR-WIoT protocol enhances and compromises the energy and delay without affecting network lifetime. The chaotic spiral dynamic (CSD) algorithm reduces the chaotic in nature of energy utilisation. Then, a queue based swarm optimisation (QSO) algorithm is utilised to next optimal node for inter cluster routing. The EDAR-WIoT protocol preserves the energy efficiency and network lifetime in wireless sensor networks. The proposed protocol is experimented using NS-2 simulator. It is observed from the experiments that the proposed protocol outperformed the other existing protocols in terms of network performance parameters.